One library to make them all: Streamlining yeast library creation by a SWAp-Tag (SWAT) strategy - Yofe, Ido; Meurer, Matthias; Knop, Michael; Khmelinskii, Anton (Nature methods, 2016)
The yeast Saccharomyces cerevisiae is ideal for systematic studies relying on collections of modified strains (libraries). Despite the significance of yeast libraries and the immense variety of available tags and regulatory elements, only a few such libraries exist as their construction is extremely expensive and laborious. To overcome these limitations we developed a SWAp-Tag method (SWAT), in which one parental library can be modified easily and efficiently to give rise to an endless variety of libraries of choice. We showcase the versatility of the SWAT approach by constructing and investigating a library of ~1,800 strains carrying a SWAT-GFP module at the amino termini of endomembrane proteins and then using it to create two new libraries (mCherry or seamless GFP). Our work demonstrates how the SWAT method enables fast and effortless creation of yeast libraries, opening the door for endless new ways to systematically study cell biology.